Simulasi Indoor Building Coverage (IBC) Pada Teknologi Long Term Evolution (LTE) Di Gedung Hindarto Joesman Fakultas Kedokteran UNJANI - Gusvira Lestari; Hajiar Yuliana; Sofyan Basuki (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
Hindarto Joesman Building, Faculty of Medicine is one of the lecture buildings at Jenderal Achmad Yani University which consists of 4 floors and has a building area of ??4125.6 m². The building has a low signal quality for the indoor LTE network. This is due to the construction and materials in the building which can weaken the quality of the LTE signal received. These conditions make the Faculty of Medicine UNJANI building require a separate indoor network installation to cover user needs inside the building. Indoor Building Coverage planning for this building can help to improve signal level and value of Reference Signal Received Power (RSRP) and Signal to Interference Noise Ratio (SINR). The process of calculating coverage planning in indoor network planning uses the Cost propagation model 231 Multi Wall Model and is simulated in the Radiowave Propagation Simulator 5.4 software. Based on the simulation results, the average RSRP value is -20.59 dBm and SINR is 34.30 dB. The average value can cover the signal quality in the building area of ??89.12% for RSRP and 97.45% for SINR. The results of the planning and simulation of the Indoor Building network have met the standard RF parameters for operators.